Innovative financing for a gender-equitable first-food system to mitigate greenhouse gas impacts of commercial milk formula: investing in breastfeeding as a carbon offset - Smith, Julie P.; Borg, Bindi; Iellamo, Alessandro; Nguyen, Tuan T.; Mathisen, Roger (Frontiers in Sustainable Food Systems, 2023)
Women’s contributions to food production and food security are often overlooked, thus perpetuating inequitable and unsustainable globalized commercial food systems. Women’s role as producers in the first-food system, breastfeeding, is largely invisible and underfunded, encouraging the production and consumption of environmentally unsustainable commercial milk formula (CMF). This policy brief highlights opportunities for including and funding interventions enabling breastfeeding under carbon offset schemes such as the United Nations Clean Development Mechanism (CDM). A Green Feeding Tool is being developed to account for the national carbon and water footprints of CMF. The tool will help ensure that women’s contributions to a sustainable first-food system are not ignored by the CDM and other mechanisms funding greenhouse gas emissions reductions.